New species and distribution records for Mexican and Central American Cerambycidae (Coleoptera) - Bezark, Larry G. (Zootaxa, 2019)
Championa santossilvai sp. nov. and Trypanidius kitayamai sp. nov. are described from Oaxaca and Veracruz, Mexico, respectively. New country records are provided for Mexico, Costa Rica and Panama. New state records for Mexico are detailed from a dozen states.